2020
DOI: 10.1002/anie.202012099
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins by Direct Annulation: β‐Borylacrylates as Ambiphilic C3‐Synthons

Abstract: Modular β‐borylacrylates have been validated as programmable, ambiphilic C3‐synthons in the cascade annulation of 2‐halo‐phenol derivatives to generate structurally and electronically diverse coumarins. Key to this [3+3] disconnection is the BPin unit which serves a dual purpose as both a traceless linker for C(sp2)–C(sp2) coupling, and as a chromophore extension to enable inversion of the alkene geometry via selective energy transfer catalysis. Mild isomerisation is a pre‐condition to access 3‐substituted cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…399 Wienhold et al have reported a modular annulation strategy to generate coumarins, such as angelicin 352, directly from 2halophenols in which β-borylacrylates serve as small, geometrically programmable, amphiphilic C 3 -synthons. 400 Isolated from the leaves of angelica archangelica, 401 coumarins and related πextended furanocoumarin natural products have found application in photochemotherapy for the treatment of skin diseases such as psoriasis. 402,403 This strategy is contingent on thioxanthone functioning as an efficient photocatalyst to enable selective energy transfer to β-borylacrylate 137 to generate 113 (66% yield and 94:6 Z/E-selectivity, Scheme 53).…”
Section: Energy Transfer-enabled Alkene Isomerization Applied To Tota...mentioning
confidence: 99%
“…399 Wienhold et al have reported a modular annulation strategy to generate coumarins, such as angelicin 352, directly from 2halophenols in which β-borylacrylates serve as small, geometrically programmable, amphiphilic C 3 -synthons. 400 Isolated from the leaves of angelica archangelica, 401 coumarins and related πextended furanocoumarin natural products have found application in photochemotherapy for the treatment of skin diseases such as psoriasis. 402,403 This strategy is contingent on thioxanthone functioning as an efficient photocatalyst to enable selective energy transfer to β-borylacrylate 137 to generate 113 (66% yield and 94:6 Z/E-selectivity, Scheme 53).…”
Section: Energy Transfer-enabled Alkene Isomerization Applied To Tota...mentioning
confidence: 99%
“… 2 , 9 , 10 Pd-catalyzed processes in particular enable a [3 + 2]heteroannulation via Pd(0)-catalyzed Buchwald–Hartwig amination 11 followed by Pd(II)-catalyzed C -arylation at a late stage in a synthetic workflow. 12 25 However, a generalized set of guidelines that control the chemoselectivity of each C–N/C–C bond-forming reaction, and the factors that influence Pd(0) 23 versus Pd(II) 17 catalysis in a one-pot process have not been established. Furthermore, a mechanistic understanding of any regiocontrol underpinning the second C–H activation step for the formation of tetracyclic carbazoles is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Carbazoles are ubiquitous N-heterocycles used throughout medicinal chemistry and material sciences. From a pharmaceutical perspective, the carbazole core features extensively in drugs and natural products, many of which exhibit potent anti-proliferative activities (Figure a). The breadth of applications has inspired the development of numerous methodologies for their preparation. ,, Pd-catalyzed processes in particular enable a [3 + 2]­heteroannulation via Pd(0)-catalyzed Buchwald–Hartwig amination followed by Pd­(II)-catalyzed C -arylation at a late stage in a synthetic workflow. However, a generalized set of guidelines that control the chemoselectivity of each C–N/C–C bond-forming reaction, and the factors that influence Pd(0) versus Pd­(II) catalysis in a one-pot process have not been established. Furthermore, a mechanistic understanding of any regiocontrol underpinning the second C–H activation step for the formation of tetracyclic carbazoles is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, palladium-catalyzed intermolecular carbonylative cyclization of o -halophenols with alkynes , or salicylic aldehydes with benzyl chlorides has been reported. More recently, Gilmour et al . has reported a Pd(0)-catalyzed cascade annulation of 2-halophenols with β-borylacrylates as ambiphilic C3-synthons to generate C3 and C4-substituted coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…37 In addition, palladiumcatalyzed intermolecular carbonylative cyclization of ohalophenols with alkynes 38,39 or salicylic aldehydes with benzyl chlorides 40 has been reported. More recently, Gilmour et al 41 has reported a Pd(0)-catalyzed cascade annulation of 2halophenols with β-borylacrylates as ambiphilic C3-synthons to generate C3 and C4-substituted coumarins. However, the transition-metal-catalyzed oxidative coupling reactions 42 are even more attractive strategies for the synthesis of heterocyclic scaffolds as coumarins, as they avoid the use of preactivated coupling partners (halides, triflates, boronates, etc.).…”
Section: ■ Introductionmentioning
confidence: 99%